Assessment of Susceptibility of Ampicillin-Resistant Enterobacteria to Cephalosporins - Greenwood, D. (1975)
The susceptibility of 103 ampicillin-resistant strains of enterobacteria to two cephalosporins was assessed by turbidimetric monitoring and disk diffusion tests. The results obtained suggest that in most cases a correlation exists between the suppression of growth of a dense bacterial culture for a therapeutically acceptable period by a fixed, high concentration of cephalosporin and a large zone of inhibition (≥24 mm) using a high potency disk. This correlation was found to hold good when a moderate, subconfluent inoculum and commercially obtained blood-agar plates were used for the disk test, but not when the stringent conditions required by the Kirby-Bauer test (which demands a dense inoculum on Mueller-Hinton agar) were employed. Better correlation was obtained with cephaloridine than with cephalothin. This approach to the interpretation of disk diffusion tests gives a grossly different picture of the susceptibility of ampicillin-resistant enterobacteria to cephalosporins than do conventional minimal inhibitory concentration-based correlations.